ANALISIS RANTAI PASOK DAN NILAI TAMBAH AGROINDUSTRI KOPI LUWAK DI PROVINSI LAMPUNG - Noviantari, Khairunnisa; Hasyim, Ali Ibrahim; Rosanti, Novi (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2015)
This research aims to determine the flow pattern of chain supply, the efficiency of marketing, and the value added on Luwak Coffee in Lampung province. This research was conducted on West Lampung region and Tanggamus region as the representative of Lampung province. A purposive method is conducted to decide the location of this research. The respondents who involved in this research were 35 people, consist of 9 coffee farmers, 7 doer of Luwak Coffee agro industry, 3 merchants of coffee, 1 big seller of coffee, 5 seller of Luwak Coffee and 10 consumer of Luwak Coffee. The first objective was answered by descriptive method, the second objective by Soekartawi’s formula of marketing efficiency, and the last objective by Hayami value added analysis method respectively. The result of this research proved that the stakeholders who involved in this chain supply of Luwak Coffee agro industry in Lampung Province were consisted of coffee farmer, merchant, seller of raw coffee beans, agro industry of Luwak Coffee, wholesalers, retailers, exporters, and consumers. The most efficient distribution was the distribution of Luwak Coffee to consumer, with the percentage of the marketing efficiency of 31.62 percent. The added value from processing of one kilogram raw coffee beans became luwak coffee beans, luwak coffee beans became a powder of luwak coffee, coffee beans became the powder of luwak coffee was 67,123.95 IDR, 78,887.87 IDR, and 42,666.01 IDR. Key words: agroindustry, supply chain, luwak coffee, added value